2012
DOI: 10.1038/nchembio.1140
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Hsp70 reduces neurotoxicity by promoting polyglutamine protein degradation

Abstract: We sought novel strategies to reduce levels of the polyglutamine androgen receptor (polyQ AR) and achieve therapeutic benefits in models of spinobulbar muscular atrophy (SBMA), a protein aggregation neurodegenerative disorder. Proteostasis of the polyQ AR is controlled by the Hsp90/Hsp70-based chaperone machinery, but mechanisms regulating the protein’s turnover are incompletely understood. We demonstrate that overexpression of Hip, a co-chaperone that enhances binding of Hsp70 to its substrates, promotes clie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
206
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(209 citation statements)
references
References 50 publications
3
206
0
Order By: Relevance
“…Hsp70 has been shown to inhibit aggregation and toxicity of a variety of amyloidogenic systems via distinct mechanisms (28)(29)(30). Here we show that hsp70 is able to protect cells against the deleterious effects of β 2 m fibril-mediated cell dysfunction to a greater extent than chemical cross-linking.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Hsp70 has been shown to inhibit aggregation and toxicity of a variety of amyloidogenic systems via distinct mechanisms (28)(29)(30). Here we show that hsp70 is able to protect cells against the deleterious effects of β 2 m fibril-mediated cell dysfunction to a greater extent than chemical cross-linking.…”
Section: Discussionmentioning
confidence: 60%
“…To determine whether fibrilinduced membrane damage can be inhibited by enhancing the kinetic stability of β 2 m amyloid fibrils, the molecular chaperone hsp70 was added. Previous studies have shown that the association of hsp70 (or its constitutively expressed homolog, hsc70) with amyloid aggregates protects against amyloid toxicity (28)(29)(30). Recombinant hsp70-1A (29) was incubated with β 2 m amyloid fibrils at pH 6.4 in a 1:0.25 or 1:3 molar ratio (monomer equivalent β 2 m:chaperone) and the effect of the chaperone on fibril stability was measured using ThT fluorescence.…”
Section: Restricting Molecular Shedding Decreases Membrane Damage Andmentioning
confidence: 99%
“…Studies with the small molecule geldanamycin (GA), a potent inhibitor of Hsp90 ATPase activity, have revealed that increases in the levels of molecular chaperones such as Hsp70 or Hsp40 are associated with reduced aggregation and toxicity of mutant HTTex1 fragments in cells and flies [36]. The importance of chaperone networks in managing misfolded proteins in cells is also supported by the effect of the compound YM-1, which increases the binding affinity of Hsp70 to polyQ disease proteins, leading to an increased efficiency of their ubiquitination and degradation [37]. High-throughput screenings have led to the identification of numerous novel small molecules that influence the expression of molecular chaperones in mammalian cells [38].…”
Section: Identification Of Small Molecules That Influence Polyq-mediamentioning
confidence: 99%
“…However, trails using antiandrogen therapy, commonly used in the treatment of advanced prostate cancer, yielded disappointing findings, despite highly promising animal studies. Other studies have shown AR:HSP70 complex and small molecules such as trehalose as a potential therapeutic target for SBMA [25,28]. Based on these studies, a potential therapeutic model can be proposed (Figure 2).…”
mentioning
confidence: 99%